PENGARUH PENGGUNAAN ROBLOX GAME SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF TERHADAP INTERAKSI SOSIAL SISWA KELAS IV DI SD NEGERI 68 PALEMBANG - Fatimah Azzahra, Cindy; Murjainah; Suriadi, Aan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether the use of Roblox Game as an interactive learning medium can improve the social interaction of fourth-grade students at SD Negeri 68 Palembang. Interactive learning media is considered one of the interesting ways to encourage students to be more actively involved in the learning process, especially in building cooperation and communication among peers. This research used a pre-experimental method with a one-group pretest-posttest design. The research subjects consisted of 21 students. Before the treatment was given, students were asked to complete a pretest questionnaire to measure their initial level of social interaction. The learning process was carried out in three meetings. The first meeting used conventional methods without any game. In the second and third meetings, students learned using Roblox games that were adjusted to the learning material. The games used were Roblox Brookhaven and Work at a Pizza Place. Students worked in small groups, and each of them took an active role during the gameplay. The researcher also provided student worksheets (LKPD) and observed their behavior while playing. After all the learning activities were completed, students filled out the posttest questionnaire. The results showed an increase in students’ social interaction after participating in the game-based learning. Students became more active in communicating, helping each other, and working together during the lessons. Therefore, Roblox Game can be used as a fun and effective alternative learning medium to develop students’ social skills.